The challenge of implementing TPS in the Czech Republic A study in cross-cultural management - Koža, Michal (2014)
This master's thesis analyzes the possibilities of implementation of Toyota Production System within Japanese subsidiaries in Czech Republic. It explores the fit between the cultural values of Czech and Japanese management and the values incorporated in the Toyota Production System. In order to conduct the study, 79 companies were contacted, and survey responses from a total of 108 Czech and Japanese employees were collected. Data from the survey show that both Czech and Japanese employees have similar values related to work and neither job satisfaction nor number of conflicts is connected with TPS training. In the conclusion, areas for further research and more detailed elaboration are identified and presented.